2016
DOI: 10.1016/j.radonc.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

ARCII: A phase II trial of the HIV protease inhibitor Nelfinavir in combination with chemoradiation for locally advanced inoperable pancreatic cancer

Abstract: Background and purposeNelfinavir can enhance intrinsic radiosensitivity, reduce hypoxia and improve vascularity. We conducted a phase II trial combining nelfinavir with chemoradiotherapy (CRT) for locally advanced inoperable pancreatic cancer (LAPC).Materials and methodsRadiotherapy (50.4 Gy/28 fractions; boost to 59.4 Gy/33 fractions) was administered with weekly gemcitabine and cisplatin. Nelfinavir started 3–10 days before and was continued during CRT. The primary end-point was 1-year overall survival (OS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
1
46
1
Order By: Relevance
“…In LAPC patients the mOS in the present analysis was roughly 20 months, which seems to be superior to the mOS rates reported in the majority of clinical trials (8.3–17.4 months; [912, 4143]). Being aware of the fact that a comparison with prospectively collected data is indirect (supplementary Table 2) a critical discussion of our findings has to consider patient selection as well as therapy regimens and toxicity.…”
Section: Discussioncontrasting
confidence: 83%
“…In LAPC patients the mOS in the present analysis was roughly 20 months, which seems to be superior to the mOS rates reported in the majority of clinical trials (8.3–17.4 months; [912, 4143]). Being aware of the fact that a comparison with prospectively collected data is indirect (supplementary Table 2) a critical discussion of our findings has to consider patient selection as well as therapy regimens and toxicity.…”
Section: Discussioncontrasting
confidence: 83%
“…It is important to note that previous dosimetric studies, which have also been less than consistent in terms of most reliable dosimetric parameters, have either studied dosimetry of SBRT alone or concurrent chemoradiotherapy; it is possible that sequential chemotherapy and SBRT could have differing dosimetric profiles due to full-course, dual-agent chemotherapy having been received prior to SBRT in this series. The addition of nelfinavir also cannot be discounted, and a complete account of clinical toxicities (especially in similar settings) has not been described aside from two reports [3031]. However, nelfinavir has no known data associated with radioprotection; though any of the gastrointestinal side effects observed herein are possible with nelfinavir, they are all quite uncommon [3031].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of nelfinavir also cannot be discounted, and a complete account of clinical toxicities (especially in similar settings) has not been described aside from two reports [3031]. However, nelfinavir has no known data associated with radioprotection; though any of the gastrointestinal side effects observed herein are possible with nelfinavir, they are all quite uncommon [3031]. Whereas many previous dosimetric studies have been retrospective in nature, a strength of this work is decreasing retrospective biases owing to prospectively collecting these data, having prespecified this secondary analysis when this clinical trial commenced accrual.…”
Section: Discussionmentioning
confidence: 99%
“…Biswa Mohan and colleagues made a preliminary study about pure honey for decreasing oral mucosal toxicity. The studies shown that topical pure honey reduces oral mucositis as dramatical [37,38]. The antioxidant, antiproliferative, antimicrobial effects of 3 to 20g of honey demonstrated in multiple studies [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The studies shown that topical pure honey reduces oral mucositis as dramatical [37,38]. The antioxidant, antiproliferative, antimicrobial effects of 3 to 20g of honey demonstrated in multiple studies [38][39][40][41][42][43]. In Islamic medicine and Iran, the combination of NS with honey is used for alleviating gastrointestinal symptoms like abdominal pain, bloating and diarrhea [44][45][46].…”
Section: Introductionmentioning
confidence: 99%